2007
DOI: 10.1291/hypres.30.1065
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Nasal Continuous Positive Airway Pressure Treatment on Plasma Adrenomedullin Levels in Patients with Obstructive Sleep Apnea Syndrome: Roles of Nocturnal Hypoxia and Oxidant Stress

Abstract: Note from the Editor-in-ChiefDuplicate publication of essentially the same data constitutes a violation of copyright law and of the ethics of scientific publication. When there is doubt about the common source, overlapping, or coincidence of data in articles that are based on the same study, the author(s) must disclose any information about their contribution being under consideration or accepted by another journal at the time of submission of a manuscript. Kazuyuki Shimada Editor-in-Chief Hypertension Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Studies on SA treatment have indicated that continuous positive airway pressure (CPAP) therapy can effectively reduce SA nocturnal hypoxia and its associated co-morbidity [35]. If overnight hypoxia in SA patients plays a major role in increased risk of BPH during follow-up, treatment such as CPAP might decrease the risk of BPH in SA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on SA treatment have indicated that continuous positive airway pressure (CPAP) therapy can effectively reduce SA nocturnal hypoxia and its associated co-morbidity [35]. If overnight hypoxia in SA patients plays a major role in increased risk of BPH during follow-up, treatment such as CPAP might decrease the risk of BPH in SA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Molecules or proteins that have been reported include leptin, intercellular and vascular adhesion molecule, L-selectin, E-selectin, interleukin-8, monocyte chemoattractant protein-1, NF-kappaB, and endothelin-1 [1,[4][5][6][7][8][9]. Nasal continuous positive airway pressure (CPAP) treatment decreases sleep apneas, nocturnal oxyhemoglobin desaturation, circulating adrenomedullin, and leukocyte production of reactive oxygen species (ROS) in OSA patients [10]. Effective uvulopalatopharyngoplasty decreases nitric oxide derivative levels [11].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular risk profiles, such as inflammatory markers in children [11,12], abnormal lipid metabolism in obese children [7••], and markers related to the development of hypertension in adults [13] reversed after treatment of SDB. QOL after treatment also improves in children with SDB, as does school performance [8••,14,15].…”
Section: The Reason To Treatmentioning
confidence: 99%
“…Hypoxemia is suggested to play a key role not only in the development of cardiovascular disorders [13] associated with SDB but also in the neuropsychological and neuronal injury associated with SDB [6]. A study comparing oxygen therapy with CPAP or placebo in 38 sleep apnea patients demonstrated significant reductions in general psychological symptoms with oxygen therapy or CPAP but not placebo; however, depression improved with oxygen and not CPAP or placebo, indicating that hypoxemia plays an important role in some symptoms occurring with SDB [78•].…”
Section: Treatment Of Blood Gas Abnormalities In Sleep-disordered Brementioning
confidence: 99%